FREQUENCY OF HELICOBACTER PYLORI IN PATIENTS WITH PRIMARY OPEN ANGLE GLAUCOMA - OOZEERKHAN, Zeeshan Khan (Pakistan Journal of Ophthalmology, 2021)
BACKGROUND Primary Open Angle Glaucoma (POAG) is one of the most common causes of irreversible pathological visual loss. Helicobacter pylori (H.pylori) is a rod that colonizes the gastric mucosa and has strong associations with diseases such as chronic gastritis, peptic ulcer and gastric carcinoma. Frequency of H.pylori in patients of POAG has not been reported in Pakistan. OBJECTIVE This study is to find out the frequency of H.pylori antibody in the serum of people with established POAG. Study Design: Cross Sectional Survey Place of study: LRBT Free Eye Hospital, Lahore. Duration: 6 months MATERIALS AND METHODS Consecutive sampling was used and informed consent and demographic information of patients was taken from 100 patients. 3ml of venous blood processed through the chemiluminescent enzyme immunoassay of the Immulite 2000 Systems Analyzers H.pylori Ig G detection kit. The Quantitative variables such as age were presented as mean and standard deviation while qualitative variables such as gender and H.pylori status (positive or negative) were expressed as frequency and percentage. RESULTS Patients’ mean age was 50.45 ± 6.16 years. There were 49 (49%) male and 51 (51%) female patients. The mean antibody level of patients was 3.80 ± 2.57 with range of 9.39. The minimum and maximum antibody level were 0.07 and 9.46 respectively. 75 (75%) patients were shown to be positive with H.pylori. CONCLUSION The study shows high frequency of H.pylori antibody in patients with Open Angle Glaucoma. Importance of this serious health concern should be investigated and eradicated at all stages of POAG.